"Don't send your sick here to be treated, our own people need it more": immigrants' access to healthcare in South Africa. Issue 1 (6th March 2017) - Alfaro-Velcamp, Theresa
Abstract : Purpose: Asylum seekers, refugees and immigrants' access to healthcare vary in South Africa and Cape Town due to unclear legal status. The purpose of this paper is to shed light on the source of this variation, the divergence between the 1996 South African Constitution, the immigration laws, and regulations and to describe its harmful consequences. Design/methodology/approach: Based on legal and ethnographic research, this paper documents the disjuncture between South African statutes and regulations and the South African Constitution regarding refugees and migrants' access to healthcare. Research involved examining South African jurisprudence, the African Charter, and United Nations' materials regarding rights to health and health care access, and speaking with civil society organizations and healthcare providers. These sources inform the description of the immigrant access to healthcare in Cape Town, South Africa. Findings: Asylum-seekers and refugees are entitled to health and emergency care; however, hospital administrators require documentation (up-to-date permits) before care can be administered. Many immigrants – especially the undocumented – are often unable to obtain care because of a lack of papers or because of "progressive realization, " the notion that the state cannot presently afford to provide treatment in accordance with constitutional rights. These explanations have put healthcare providers in an untenable position of not being able to treat patients, including some who face fatal conditions. Research limitations/implications: The research is limited by the fact that South African courts have not adjudicated a direct challenge to being refused care at healthcare facility on the basis of legal status. This limits the ability to know how rights afforded to "everyone" within the South African Constitution will be interpreted with respect to immigrants seeking healthcare. The research is also limited by the non-circulation of healthcare admissions policies among leading facilities in the Cape Town region where the case study is based. Practical implications: Articulation of the disjuncture between the South African Constitution and the immigration laws and regulations allows stakeholders and decision-makers to reframe provincial and municipal policies about healthcare access in terms of constitutional rights and the practical limitations accommodated through progressive realization. Social implications: In South Africa, immigration statutes and regulations are inconsistent and deemed unconstitutional with respect to the treatment of undocumented migrants. Hospital administrators are narrowly interpreting the laws to instruct healthcare providers on how to treat patients and whom they can treat. These practices need to stop. Access to healthcare must be structured to comport with the constitutional right afforded to everyone, and with progressive realization pursued through a non – discriminatory policy regarding vulnerable immigrants. Originality/value: This paper presents a unique case study that combines legal and social science methods to explore a common and acute question of health care access. The case is novel and instructive insofar as South Africa has not established refugee camps in response to rising numbers of refugees, asylum seekers and immigrants. South Africans thus confront a "first world" question of equitable access to healthcare within their African context and with limited resources in a climate of increasing xenophobia.